Determinasi Kinerja Karyawan: Analisis Lingkungan Kerja, Beban Kerja dan Kepemimpinan pada PT Graha Sarana Duta - Farhan Saputra; Alifah Jiddal Masyruroh; Bayu Putra Danaya; Srirahayu Putri Maharani; Nova Astia Ningsih; Tania Septfania Ricki; Ganis Aliefiani Mulya Putri; Jumawan Jumawan; Hadita Hadita (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to see the influence of the work environment, workload and leadership on employee performance at PT Graha Sarana Duta. The independent variables in this research include work environment, workload and leadership, and the dependent variable in this research is employee performance. The population in this study was 211 people, namely employees at PT Graha Sarana Duta. The sample in this study was 100 people. The sampling technique uses accidental sampling. The data collection method used in this research uses a questionnaire method. The design used in this research is Outer Model testing, Inner Model testing, hypothesis testing using Structural Equation Model (SEM) – SmartPLS 3.0. The results of this research show that: 1) The work environment has no effect on the performance of PT Graha Sarana Duta employees; 2) Workload has a positive effect on the performance of PT Graha Sarana Duta employees; and 3) Leadership influences the performance of PT Graha Sarana Duta employees.